Pendampingan Penggunaan Aplikasi Budgeting Pada PT Jaya Selalu Juwana Jawa Tengah Guna Meningkatkan Pendapatan Usaha - Sari, Putri Oktovita (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The emerging issue in the latest technological advancements has become the most powerful mechanism for advancing living standards and environmental sustainability in the era of the 4.0 revolution, leading to the Society 5.0 era. The combination of technology, which also focuses on humans, will be balanced to advance economic growth. PT Jaya Selalu Juwana, located in Central Java, is a cold storage company engaged in the export of fresh products. This dedication to society is expected to increase knowledge and utilize technological advancements packaged through an application called